Deviasi Orientasi Gerakan Dakwah Partai Keadilan Sejahtera - Wiryo Setiana (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2015)
The strategy of PKS as a da’wah party in the transformation of the nation, is a cultural movement and structural movement. Horizontal mobilization to spread of cadres in various groups and segments of society to prepare the community so they receive manhaj Islam and Islamic policy products. In general, the basic policy principles adopted by PKS reflected fully in their identity as Da'wah Party. While proselytizing is believed PKS is proselytizing rabbaniyah rahmatan lil'alamin, that proselytizing is guiding people to know God and proselytizing is addressed to all mankind that bring solutions to the problems it faces. He is da'wah fair towards brotherhood among mankind, far from forms of racism or bigotry ethnicity, race, or ethnicity.